EVALUATING THE RIGHT TO EDUCATION: AN ANALYSIS OF THE RTE ACT 2009, ITS IMPLEMENTATION, AND IMPACT ON AGENCY AREAS IN TELANGANA (International Journal of Food and Nutritional Sciences, 2023)
This paper deals an illuminating perception of the Right of Children to Free and Compulsory Education Act, 2009 (RTE Act) – and its implementation and effects on India with emphasis on the agency areas in Telangana. This paper explores the provinces and acts implemented under the Act in addressing legal provisions, key provisions, and operationalization of mechanisms under the Act among the central and state governments. This way, the study evaluates the impact of the Act on enrollment rates, as well as on learners’ retention, and the quality of education by combining findings of quantitative analysis of educational indicators with the results of qualitative analysis of case studies. The study proved increased capacities in relation to access to education and Agency infrastructure development but reveals that inclusive challenges still remain; including teacher scarcity, Cultural impediments, and resource scarcities. The present paper adduces qualitative case evidence from Telangana that may offer finer-grained understanding of the enabling environment and reveal instances of both best practice improvement and ongoing challenge. In the end, their policy implications for the improvement of the Act’s effectiveness, especially in vulnerable population groups, and a focus on the importance of the Act for the development of educational equality and inclusiveness in India are presented.